Molecular characterization of cancer reveals interactions between ionizing radiation and chemicals on rat mammary carcinogenesis. Issue 7 (8th October 2013) - Imaoka, Tatsuhiko; Nishimura, Mayumi; Doi, Kazutaka; Tani, Shusuke; Ishikawa, Ken‐ichi; Yamashita, Satoshi; Ushijima, Toshikazu; Imai, Takashi; Shimada, Yoshiya
<x xml:space="preserve">Abstract</x> Although various mechanisms have been inferred for combinatorial actions of multiple carcinogens, these mechanisms have not been well demonstrated in experimental carcinogenesis models. We evaluated mammary carcinogenesis initiated by combined exposure to various doses of radiation and chemical carcinogens. Female rats at 7 weeks of age were γ‐irradiated (0.2–2 Gy) and/or exposed to 1‐methyl‐1‐nitrosourea (MNU) (20 or 40 mg/kg, single intraperitoneal injection) or 2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐b]pyridine (PhIP) (40 mg/kg/day by gavage for 10 days) and were observed until 50 weeks of age. The incidence of mammary carcinoma increased steadily as a function of radiation dose in the absence of chemicals; mathematical analysis supported an additive increase when radiation was combined with a chemical carcinogen, irrespective of the chemical species and its dose. Hras mutations were characteristic of carcinomas that developed after chemical carcinogen treatments and were overrepresented in carcinomas induced by the combination of radiation and MNU (but not PhIP), indicating an interaction of radiation and MNU at the level of initiation. The expression profiles of seven classifier genes, previously shown to distinguish two classes of rat mammary carcinomas, categorized almost all examined carcinomas that developed after individual or combined treatments with radiation (1 Gy) and chemicals as belonging to a single class; more comprehensive screening using microarrays and a separate test sample set failed to identify differences in gene expression profiles among these carcinomas. These results suggest that a complex, multilevel interaction underlies the combinatorial action of radiation and chemical carcinogens in the experimental model.